Adopting the Blue Green Economy Term to Achieve SDGs in Digital Learning: Opportunities and Challenges for Indonesia - Sungkawati, Endang; Uthman, Yusuf Olawale Owa-Onire (Assyfa Learning Journal, 2024)
This study examines the adoption of the "Blue Green Economy" concept to achieve the Sustainable Development Goals (SDGs) through digital learning in Indonesia. Utilizing a systematic literature review (SLR), this research analyzes 50 peer-reviewed articles focusing on the integration of Blue Green Economy principles into digital education. The methodology includes stringent inclusion and exclusion criteria to ensure the reliability and validity of the findings. Key opportunities identified include the potential for digital platforms to disseminate environmental education widely and the role of innovative technologies in promoting sustainable practices. Challenges highlighted encompass inadequate digital infrastructure, limited educator training, and resource scarcity. The study specifically addresses SDGs 4 (Quality Education), 9 (Industry, Innovation, and Infrastructure), and 13 (Climate Action), demonstrating how the Blue Green Economy can facilitate these goals. Recommendations for overcoming challenges include government policies to enhance digital infrastructure, private sector investment in educational technology, and community-driven initiatives for teacher training. By fostering collaboration among stakeholders, this study posits that the Blue Green Economy can be effectively integrated into digital learning, thus supporting both environmental and economic sustainability in Indonesia.